The temporal and mythological interlacements of the presence of ancient goddesses in the Kaguya character in anime Naruto Shippuden (Palíndromo, 2022)
Japanese animations, known as anime, are produced for diverse and popular audiences outside of Japan, as is the case of Brazil. Some of these animations use narratives and mythological images that can be identified by the study of historical allegory (BENJAMIN, 1984), present in the narrative, in its images and, mainly, emanated by the presence of multiple temporalities, which shows the anachronism of images (DIDI-HUBERMAN, 2011). This is the case of the character Kaguya from the anime Naruto Shippuden. This character conveys cultural and mythological interlacements that is linked to the figure of the goddess present in ancient mythologies. The goal is to analyze the transtemporal presences of the goddess image transmitted by the character Kaguya in the anime Naruto Shippuden. For this, the concepts of historical allegory (BENJAMIN, 1984), past presences (GUMBRECHT, 2010) and anachronism (DIDI-HUBERMAN, 2011) will be used.
Keywords: Kaguya; Goddess; Mythology; Naruto